Persepsi Wajib Pajak atas Kemudahan Sistem Coretax terhadap Pelaporan SPT Tahunan dan Implikasinya terhadap Kepatuhan: Studi Kualitatif pada Kantor Pelayanan Pajak Pratama Demak dan Kantor Pelayanan Pajak Pratama Blora - Fatikatul Khofiafah; Inaya Rahma Nafisa Nafisa; Syarifatul Putri Astari; Luklu'a Farida Annur; Livia Azzisatul Laila; Herwening Sindu Lestari (LKP KARYA PRIMA KURSUS, 2026)
This study aims to analyze taxpayers’ perceptions of the ease of using the Coretax system in filing Annual Tax Returns (SPT Tahunan) and its implications for taxpayer compliance. The study employs a qualitative approach with a case study design at the Demak and Blora Primary Tax Service Offices (KPP Pratama) through in-depth interviews and literature review, using the Miles and Huberman data analysis model. The findings indicate that Coretax provides convenience through features such as prepopulated data, data integration, and reporting efficiency, which are able to improve taxpayer compliance, particularly formal compliance. However, several obstacles remain, including system complexity, technical disruptions, and limited user understanding, which hinder the optimization of its use. In addition, in terms of material compliance, there is still potential for errors caused by data inconsistencies and a lack of understanding of the reporting flow. Therefore, perceived ease of use plays an important role in improving taxpayer compliance, making system refinement, enhanced socialization, and adequate technical support necessary so that Coretax implementation can run optimally and sustainably.